Frontiers on Sustainable Food Packaging - Varzakas, Theodoros; Cruz, Rui M.S (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The purpose of this Special Issue was to attract papers in the new era of sustainability and food packaging that address all major sectors of the food industry from cereals and confectionery to fruits and vegetables, meat, and dairy products.